2014
DOI: 10.1111/radm.12066
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of business model development in the commercialization of technology innovations

Abstract: Research on business model development has focused on the relationships between elements of value conceptualization and organization having a linear sequence in which business models are first designed and then implemented. Another stream of research points to business model development with these elements interacting in a cyclical manner. There is a need to improve our understanding of the connective mechanisms and dynamics involved in business model development, particularly from the challenging perspective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 48 publications
2
72
0
1
Order By: Relevance
“…Sinfield et al, 2012;Taran et al, 2015), two elements (e.g. Mason and Spring, 2011; Dmitriev et al, 2014). However, very few included three or more elements (e.g.…”
Section: Operational Valuementioning
confidence: 99%
“…Sinfield et al, 2012;Taran et al, 2015), two elements (e.g. Mason and Spring, 2011; Dmitriev et al, 2014). However, very few included three or more elements (e.g.…”
Section: Operational Valuementioning
confidence: 99%
“…Consequently, the development of a business model is described in terms of experimentation (Andries et al, 2013), trial-and-error learning (Chesbrough, 2010;Sosna et al, 2010) and the need for flexibility (Bock et al, 2012). Dmitriev et al (2014) found that each business model component may furthermore receive attention at different moments during the development process. Moreover, alternative business models are often created in parallel (Casadesus-Masanell and Tarzijan, 2012).…”
Section: Business Model Development Process Of New Technology-based Vmentioning
confidence: 99%
“…Business model innovation has recently become an important topic for firms as it provides an opportunity to benefit from new technological developments (Chesbrough and Rosenbloom, ; Dmitriev et al, ) and to reshape business activities (Teece, ; Amit and Zott, ; Casadesus‐Masanell and Zhu, ; Demil et al, ). Especially in mature industries where options to innovate products and processes are limited (Oliva and Kallenberg, ), business model innovation is said to provide a – compared to product and process innovation – cost‐ and time‐efficient opportunity to improve a firm's competitive position (Amit and Zott, ).…”
Section: Introductionmentioning
confidence: 99%